Perancangan Kampanye Sosial mengenai Penyalahgunaan Akun Palsu untuk Cyberbully - Laurencia Baskarani (Wimba : Jurnal Komunikasi Visual, 2021)
In this digital era, nearly all people are using social media. It gives so many features that can help people, one of them is about communication, but those features can also be misused. Being one of the features, anonymity is a condition where one identity cannot be identified. A person can be using disguised or fake identity. By being anonymous, one can make fake account to hide their identity. If this act is being done without the responsibility of its owner, it can form bad intention to be used against other social media user. Information regarding teenagers as the target were analyzed based on surveys and interviews, while information about anonymity were collected through literature studies and interview with a sociologist. The data were compiled as information to support the social campaign. Those information about raising target's awareness in relation to the misuse of fake account in social media are delivered through a social campaign with major campaign activity are focused on social media. To prevent the misuse of fake account that can cause cyberbully, the campaign is expected to bring the awareness to the target thus they can start to express their opinion in an assertive way while communicating with other internet users. Keyword: cyberbully, social campaign, social media, teenager